MO776: Central Tunnelled Catheter Implantation by a Multidisciplinary Nephrology and Radiology Team: 10-Year Experience. (3rd May 2022) - Rodríguez Farré, Neus; Núñez Delgado, Sara; Calaf Forn, Francesc; Pelegrí Martínez, Laura; Rap Copindean, Oana; Sánchez Escuredo, Anna; Cabrera López, Cristina; Giménez Torrecilla, Isabel; Ibernon Vilaro, Meritxell; Pilar Ruiz Valverde, Maria
Abstract: BACKGROUND AND AIMS: Insertion of tunnelled central venous catheters (TCVC) in patients with chronic kidney disease requiring haemodialysis is a technique of increasing interest in interventional nephrology. Ambulatory placement by a multidisciplinary team of nephrologists and radiologists reduces immediate complications among these patients. METHOD: Retrospective study of TCVC implantation from 2011 to 2021. The ultrasound-guided technique was used for localization and venipuncture. Correct catheter location and venous anatomy were subsequently checked by fluoroscopy. Early adverse events (30 days post-placement) were recorded. RESULTS: A total of 427 TCVC were placed in 344 patients during this period. Out of these 248 (58.07%) were primary placements (PP) and 179 (41.92%) guidewire exchanges over previous catheter (GE). A total of 406 (95.08%) TCVC were placed in the internal jugular and 374 (87.59%) TCVC with right laterality. During the follow-up period, early minor complications were recorded in 23 procedures (5.39%), 15 of which (3.51%) required catheter replacement. Patients with GE developed more complications (P 0.039), being venous stenosis, the main complication described (Figure). A total of 61 patients required successive catheter placements: 48 (78.69%) underwent two procedures and 13 (21.31%) more than three procedures, for a total of 83 TCVC. There were no differences in the number of early complications between the first (10) and successive (14) placements (P 0.94). Catheter durability was similar in subsequent procedures (355 ± 62.3 days at first placement versus 459 ± 60.3 days in successive placements, P 0.24). CONCLUSION: Multidisciplinary TCVC implantation guarantees good effectiveness of the technique. The performance of subsequent procedures is safe and durable in patients with CKD.